Provisional Survey of Functional Training at Elderly Daycare Service Facilities in the Inba Area of Chiba Prefecture - SAKURAI, Yoko; MORII, Kazue (Rigaku ryoho kagaku, 2022)
[Purpose] There are many circumstances where non-rehabilitation professionals provide functional training at daycare services. This study aimed to clarify the actual situations and problems in facilities without rehabilitation specialists by investigating their responses to a questionnaire survey. [Participants and Methods] The questionnaire survey was sent to 196 daycare service facilities in the Inba area of Chiba Prefecture. Responses were collected from facility staff who were in charge of deciding the contents of functional training. [Results] Thirty-nine daycare service facilities returned the survey. The results show that 80% of the daycare service facilities provided functional training and risk management, and 40% of them employed rehabilitation specialists. About 65% of daycare service facilities that provided functional training said they were concerned about decisions on functional training programs. [Conclusion] Since the elderly have a wide range of physical functions that require complicated management of risk, it seems facilities commonly have worries concerning functional training regardless of the professions involved.